Studi sulla terminologia linguistica - Palombo, Luca; Perrelli, Raffaele; Gomez Gane, Yorick (Università della Calabria, 2024)
The research project conducted during the three years of the doctoral course led to the realization of historical-linguistic studies and insights into the terminology of Italian linguistics. The interest reserved for the diachronicaspect in this lexicographic study is functional to the reconstruction of the history of linguistic phenomena and practices, with the aim of investigating the history of the discipline through its words. The first part of the work was oriented toward the constitution of a basic lemmary of linguistic terminology, obtained through the perusal of Tullio De Mauro's Grande dizionario italiano dell'uso (Turin, UTET 2007), from which it was possible to extrapolate more than three thousand monorematic and polyrematic headwords. The deduced material, which is extremely heterogeneous, was later subdivided into further categories and subcategories, identified on an exclusively semantic basis. This classification work is preparatory to the constitution of a historical vocabulary of linguistic terminology, the basic corpus of which can be constituted from the GRADIT database and supplemented through other lexical reference directories and specific linguistic studies. In particular, the perusal of digital editions of Zingarelli. Vocabolario della lingua italiana (Bologna, Zanichelli 2022) and the Nuovo Devoto- Oli. Vocabolario dell'italiano contemporaneo (Milan, Le Monnier 2022) brought new lexical material to the basic lemmary. The subdivision of the material within semantically homogeneous groups also made it possible to identify deficiencies and omissions in De Mauro's Dictionary, and consequently the opportunity on the one hand to supplement and point out cases of lexicographical inconsistencies, and on the other hand to examine groups of words according to specific individual treatments, through corpora constituted on the basis of manuals and linguistic studies on the subject. Some particular aspects and directions within Italian linguistic studies have been chosen: text linguistics (Ch. II), grammar of valency (Ch. IV), terminology of etymological research (Ch. V) and terminology of sociolinguistics (Ch. VI). However, chapters III and VII constitute partially different treatises from the others. In III I dealt with the history of a single technicism, logonimo ‘logonym’, a neologism introduced in 1997 whose history and fortune I reconstructed. In Chapter VII, on the other hand, I dealt with a number of paragraphemic signs and the technical value they have taken on in the field studies, with particular reference to the different uses of the asterisk – in historical and descriptive linguistics – and the small caps. Each of the terminological groups was compared and integrated first of all with sectoral lexicography, which in Italy has had considerable development only since the late 1960s. Two distinctive directions can be distinguished in Italian linguistic lexicography. On the one hand are the works that appeared in Italian as translations of foreign works: Jean Dubois's Dictionary of Linguistics (Bologna, Zanichelli 1979), Hadumod Bußmann's Lexicon of Linguistics (Alessandria, Edizioni dell'Orso 2007), but also the third edition of Jules Marouzeau's Lexique de la terminologie linguistique (Paris, Geuthner 1951), which – although written in French and thus intended for a mainly French-speaking audience – presents the translation of lemmas into Italian, edited by Bruno Migliorini and Amerindo Camilli. On the other hand, the lexicons produced by Italian linguists, such as Agostino Severino's Manuale di nomenclatura linguistica (Milan, Le lingue estere 1937), the glossary of structuralist structure Linguistica generale (Rome, Armando 1969), the broader Dizionario di linguistica (Rome, Armando 1988), both by Giorgio Raimondo Cardona, and finally the Dizionario di linguistica edited by Gian Luigi Beccaria (Turin, Einaudi 2004, first ed.1994). As we have seen, these repertories cover a period from 1937, the year of the publication of Severino's Handbook, to 2007, the year in which the translation of Bußmann's Lexicon appears, and thus constitute inherently diachronic tools through which it is possible to sift through changes and aporias in linguistic terminology. The comparison of lexicographical repertoires is also linked to the specific study on individual words and phrases, so different text corpora have been constituted in the different chapters, depending on the subject matter. These corpora consist both of studies with a manualistic slant, which are useful for an overview of specific terminology in synchronicity, and of contributions in journals, which are instead useful for a diachronic study. Lastly, each chapter is complemented by a small historical glossary of the terms examined, whose objective is not to trace the first ever attestation of the terms, an operation that is moreover difficult in many cases, nor more generically to point out their backdating, but rather to restore historical depth to the terms treated, documenting and historicizing their uses.
Dottorato internazionale di ricerca in Studi umanistici: Testi, saperi, pratiche: dall'antichità classica alla contemporaneità, Ciclo XXXVI, a.a. 2023-2024
Keywords: Lessicigrafia; Lessicologia; Terminologia; Storia della lingua; Linguistica